Coal in our Veins : A Personal Journey - Thomas, Erin Ann (Book collections on Project MUSE., 2012)
Coal in Our Veins employs historical research, autobiography, and journalism to intertwine the history of coal, her ancestors' lives mining coal, and the societal and environmental impacts of the United States' dependency on coal as an energy source. In the first part of the book, she visits Wales, native ground of British coal mining and of her emigrant ancestors. The Thomases' move to the coal region of Utah, where they witnessed the Winter Quarters and Castle Gate mine explosions two of the worst mining disasters in American history and the history of coal development in Utah are explored in the second part.